CONTEXTUAL APPROACH TO LITERARY CRITICISM: DOSTOEVSKY AND PSYCHOANALYSIS - V. G. Kalashnikov (Russian State Vocational Pedagogical University, 2016)
The aim of this article is to demonstrate the possibilities of application of the contextual approach, developed in pedagogy and psychology, in the process of literary analysis. Initially contextual approach was developed by A. A. Verbitsky as a methodology of education. A key category of this approach was the context, interpreted A. A. Verbitsky as a psychological phenomenon. Accordingly, in this paper on the basis of later research context is understood as a psychological mechanism of semantic, objectified in external forms of test patches, social and communicative situations, etc. Now contextual approach became general psychological methodology, which led to the possibility of its application in various fields of the humanities in particular - in psycholinguistic literary studies, where the notion of «context » is used in-depth psychological interpretation. Methods. The contextual approach developed by A. A. Verbitsky as the main component of methodology of education became the main instrument of the research stated in the publication. Besides a field of the general education, this approach is applicable to various private spheres - to educational aspect of education, and also to methodology of teaching various subject matters - mathematicians, biology, foreign languages, etc. The contextual approach at the level of allpsychological methodology has allowed to apply it in various fields of humanitarian knowledge, in particular in literary researches with a strongly pronounced psychological perspective. The contextual analysis corresponding to approach has been chosen as a method of work.Results. Based on A. A. Verbitsky's interpretation and results of the latest researches the author shows that the context is a semantic mechanism, objectified in external forms of test fragments, social and communicative situations, etc. The following types of contexts are allocated: microcontext of a personality and works of an author, a mesocontext of socio-cultural influences, and also macrocontext of perception and interpretation of works in culture and science. The critical view of psychoanalysis as the literary criticism tool in the Russian culture is presented. Through the systematization of complementary contexts and psychoanalytic interpretation the myth about F. M. Dostoyevsky's epilepsy as a source of his creativity is discredited; though by recognition of the writer, personal problems and neuroses nevertheless were reflected in his works. The hypothesis of the opposite influence of creativity of F. M. Dostoyevsky on S. Freud's concept, i.e. formation of psychoanalysis under impact of art creativity is made.Scientific novelty. Methods of engaging of an intertextual and socio-cultural environment are known in linguistics and literary criticism long ago. However, diverse environments of existence of the personality and works of the artist as the unified system of contexts psychological in essence have not been considered yet. The novelty of the proposed way of a research consists in systematicity of formation of a complex of contexts of the studied phenomenon that makes it possible to correlate the diversified information through its origin. As a result, the researcher receives a number of complementary descriptions in the spirit of «the principle of a complementarity» by N. Bohr that provides dimensions and completeness of perception of the studied phenomenon.Practical significance of the work lies in the hard proof of the prospects of the contextual approach to interdisciplinary psychological and literary research.